1995
DOI: 10.1029/94ja02938
|View full text |Cite
|
Sign up to set email alerts
|

Observations in the vicinity of substorm onset: Implications for the substorm process

Abstract: Multi-instrument data sets from the ground and satellites at both low and high altitude have provided new results concerning substorm onset and its source region in the magnetosphere. Twenty-six out of 37 substorm onset events showed evidence of azimuthally spaced auroral forms (AAFs) prior to the explosive poleward motion associated with optical substorm onset. The azimuthal wavelengths associated with these onsets were found to range between 132 and 583 km with a mean value of 307 _+ 115 km. The occurrence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 67 publications
15
120
0
Order By: Relevance
“…From this more detailed perspective, we can clearly see that the intensified onset region in the 14:02:12 UT image is comprised of a sequence of azimuthally periodic bright spots, and that these bright spots lie precisely on-top of the pre-existing growth phase arc. Such spatially periodic auroral spots have been seen prior to the onset of substorm expansion phase in other studies as well (Henderson, 1994;Elphinstone et al, 1995;Samson et al, 1996;Voronkov et al, 2000Voronkov et al, , 2003. In addition, no distortions of the more poleward emissions are evident in the auroral images.…”
Section: Observationsmentioning
confidence: 53%
See 1 more Smart Citation
“…From this more detailed perspective, we can clearly see that the intensified onset region in the 14:02:12 UT image is comprised of a sequence of azimuthally periodic bright spots, and that these bright spots lie precisely on-top of the pre-existing growth phase arc. Such spatially periodic auroral spots have been seen prior to the onset of substorm expansion phase in other studies as well (Henderson, 1994;Elphinstone et al, 1995;Samson et al, 1996;Voronkov et al, 2000Voronkov et al, , 2003. In addition, no distortions of the more poleward emissions are evident in the auroral images.…”
Section: Observationsmentioning
confidence: 53%
“…We note that the event examined here is very similar to a handful of events that have been studied in the past. Early examples obtained with the Viking UV imager have been presented (Henderson, 1994;Elphinstone et al, 1995) and more recently, a few cases from ground-based imagers have been reported (Voronkov et al, 2003;Donovan et al, 2006). Two of the clearest substorm onsets showing arc-aligned azimuthally periodic bright spots from the Viking imagery occurred on 24 November 1986 at 10:12:11 UT and on 23 September 1986 at 20:51:46 UT.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the slowly moving beads in the first stage have never been reported in previous studies [Donovan et al, 2006;Sakaguchi et al, 2009]. Very recently, Kataoka et al [2011], using an electron multiplier charge-coupled device (EMCCD) camera with a narrow FOV, demonstrated that smaller-scale auroral forms (on a scale of a few/several km) appear in a breakup arc in a few minutes before onset.…”
Section: Discussionmentioning
confidence: 99%
“…However, the abovementioned interhemispheric similarities strongly suggest that there must be a common driver in the magnetotail equatorial region that was controlling the major temporal evolution of the auroral beads. Most of the previous studies of auroral beads [e.g., Donovan et al, 2006;Liang et al, 2008] inferred that the magnetospheric driver of the auroral beads may be a ballooning type instability [Cheng, 2004]. Of course, some different processes at a lower altitude along the field line (i.e., M-I coupling region) may also contribute to the structuring of the bead structures: for example, ionospheric feedback instability in the so-called ionospheric Alfven resonator [Lysak and Song, 2002] and instabilities in the auroral acceleration region [Chaston and Seki, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation